ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI UBI KAYU DI KECAMATAN BLAMBANGAN PAGAR KABUPATEN LAMPUNG UTARA - Ertania Yusnani Saputri; Dwi Haryono; Teguh Endaryanto (Lampung University, 2022)
This research aims to analyze the factors that affect the production of cassava farming and cassava farming income in the Blambangan Pagar sub-district North Lampung District. The research was conducted in Blambangan Pagar Sub-district North Lampung District. This research method is a survey method with purposive sampling technique and random sampling. Respondents in this research consisted of 70 raspondents divided into two villages, 37 respondets in Pagar Gading Village and 33 respondents in Blambangan Village. This research uses Cobb-Douglass production factors analysis method and R/C ratio income analysis. Data collection was carried out from February 2021 to March 2021. The results showed that the factors that influenced the production of cassava farming in the Blambangan Pagar Sub-district were land area, seeds, ures fertilizer and phonska fertilizer. The income for cassava farming in Blambangan Pagar Sub-district obtained an acceptane ratio or R/C for a total cost of more than 1, namely 1,45, wich means that cassava farming is profitable and feasible to cultivate.Keywords: Cassava, farming, Income, production